DESIGN OF MOTORCYLE ACTIVE CHASSIS GEOMETRY CHANGE SYSTEM (Perner's Contacts, 2011)
Modern motorcycles have a number of electronic systems supporting their driving stability. These are usually adopted solutions used in automobiles. However, the idea of trying to affect the driving stability with the use of up-to-now changeless parameters such as wheelbase or trail is quite new. Such an innovative solution of motorcycle suspension with variable geometry dependent on driving conditions was designed in thesis by Jakub Šmiraus and constructed at the Institute of Transport VŠB - Technical university of Ostrava under tutelage of MSc Michal Richtář.
Keywords: Motorcycle dynamics; motorcycle suspension; variable suspension; variable trail; active motorcycle geometry chassis; trail